Barriocide: Investigating the Temporal and Spatial Influence of Neighborhood Structural Characteristics on Gang and Non-Gang Homicides in East Los Angeles. (November 2017) - Valasik, Matthew; Barton, Michael S.; Reid, Shannon E.; Tita, George E.
This study explored how changes in neighborhood structural characteristics predicted variation in gang versus non-gang homicides in a policing division of the Los Angeles Police Department (LAPD). Longitudinal negative binomial models were examined to test the relationship between-neighborhood structural covariates with gang and non-gang homicides over a 35-year period. This study highlights the potential to estimate temporal effects not captured by cross-sectional analyses alone. The results underscore a unique feature that distinguishes gang homicides from other forms of non-gang violence, its tenacious clustering, and spatial dependence over time.